The shape of business cycles: A cross‐country analysis of Friedman's plucking theory. - Kohlscheen, Emanuel; Moessner, Richhild; Rees, Daniel M. (Kyklos, 2024)
We test the international applicability of Friedman's plucking theory of the business cycle in 18 advanced economies between 1970 and 2019. We find that in countries where labour markets are more flexible (Australia, Canada, Denmark, Switzerland, United Kingdom, United States), unemployment rates typically return to pre‐recession levels, in line with Friedman's theory. Elsewhere, unemployment rate recoveries are less complete. Output recoveries differ less across countries, but more across episodes: on average, half of the decline in GDP during a recession persists. In contrast, the extent of labour market tightening or output growth during a boom generally does not provide any information about the intensity of the subsequent recession. In terms of sectors, declines in manufacturing are typically fully reversed. In contrast, construction‐driven recessions, which are often associated with bursting property price bubbles, tend to be persistent.